The relationship between environmental ethics literacy and the caracteristics of environmental awareness of biology pre-service teachers - Hudha, Atok Miftachul; Aini, Firda; Miharja, Fuad Jaya (Biosfer: Jurnal Pendidikan Biologi, 2024)
Behavior that damages the environment can be changed through knowledge, because knowledge can influence a person's attitude in protecting theenvironment. This research aims to analyze the relationship between environmental ethics literacy and environmental awareness in prospective biology teacher students. The research was conducted on Biology Education students at "X" University, Malang City. The research sample was taken randomly from the population and the sample in this study was 74 prospective biology teacher students in semester V of the 2020/2021 academic year, and semester VII of the 2019/2020 academic year. Sample selection was based on all students who had taken and passed ethics andecology courses. The instruments used to collect data were test questions and attitude observation sheets with Likert scales and Guttman scales. Data were analyzed using the Pearson Product Moment correlation test with data processing using the SPSS 24 for Windows program. Theresearch results show that (1) the environmental ethics literacy of prospective biology teacher students is in the medium category; (2) environmental awareness of prospective biology education teacher students in the good category; (3) there is a relationship betweenenvironmental ethical literacy and environmental awareness character, because the results of correlation analysis with the Pearson ProductMoment correlation show a significance value of 0.000 < 0.05. The results of this research show that environmental ethics literacy has a positiverelationship with environmental awareness, so to foster environmental awareness it is necessary to continuously increase environmental ethics literacy.